2015
DOI: 10.3390/ijms16034362
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Evaluation of Biodiesel Production from Waste Cooking Oil—A Case Study of Hong Kong

Abstract: Fossil fuel shortage is a major challenge worldwide. Therefore, research is currently underway to investigate potential renewable energy sources. Biodiesel is one of the major renewable energy sources that can be obtained from oils and fats by transesterification. However, biodiesel obtained from vegetable oils as feedstock is expensive. Thus, an alternative and inexpensive feedstock such as waste cooking oil (WCO) can be used as feedstock for biodiesel production. In this project, techno-economic analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 20 publications
4
68
0
Order By: Relevance
“…Some studies report consecutive reactions as a way to improve the ester yield [92,93]. For the waste cooking oil, prices of 0.28-0.42 US$/kg have been adopted [41,97].…”
Section: Other Potential Feedstock: Waste Oils Non-edible Oils and Omentioning
confidence: 99%
“…Some studies report consecutive reactions as a way to improve the ester yield [92,93]. For the waste cooking oil, prices of 0.28-0.42 US$/kg have been adopted [41,97].…”
Section: Other Potential Feedstock: Waste Oils Non-edible Oils and Omentioning
confidence: 99%
“…WCO released directly into sewage pipes will cause congestion in sewer lines; when entering sewage treatment plants, it generates operational troubles or system overloading because lipids are very difficult to decompose, and are therefore causes of soil and water pollution [4]. Many recent studies on biodiesel production from WCO have revealed the great potential of this feedstock compared with first-generation biodiesel in terms of resolving environmental, economic, and social issues simultaneously [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…FCI incorporated direct costs (e.g., equipment delivery, installation, instrumentation controls, piping, electrical system, building, yard improvement, and service facilities) and indirect costs (e.g., engineering and supervision, construction expenditure, legal expenditure, contractor's fees, and contingency) . The total cultivation area cost (TCAC) and working capital (WC) were covered under TCI (Table ) . Figure shows the distribution of TCI.…”
Section: Resultsmentioning
confidence: 99%